2018
DOI: 10.1111/maps.13113
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive imaging of hypervelocity impact‐induced damage zones beneath laboratory‐created craters by means of ultrasound travel‐time tomography

Abstract: Since the 1960s, hypervelocity impact experiments have been conducted to study the complex deformation mechanisms which occur in the subsurface of meteorite craters. Here, we present ultrasound tomography measurements of the damage zone underneath seven experimentally produced impact craters in sandstone cubes. Within the framework of the Multidisciplinary Experimental and Modeling Impact Research Network and the NEOShield Project, decimeter‐sized sandstone targets were impacted by aluminum and steel projectil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…For example, Moser et al. () found for sandstone targets that a reduction of ultrasound velocities correlated with subsurface damaging at much deeper depths within the target than observed by microanalysis (see also Raith et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Moser et al. () found for sandstone targets that a reduction of ultrasound velocities correlated with subsurface damaging at much deeper depths within the target than observed by microanalysis (see also Raith et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, further microscopic studies, as well as ultrasound measurements, could hint at the reliability of the model data in predicting deep-lying deformation features. For example, Moser et al (2013) found for sandstone targets that a reduction of ultrasound velocities correlated with subsurface damaging at much deeper depths within the target than observed by microanalysis (see also Raith et al, 2018).…”
Section: Quartzitementioning
confidence: 99%
“…Micro‐computed tomography is capable of tracing large spall cracks and concentric fractures below the crater surface of the experimentally impacted sandstone blocks. Ultrasound tomography revealed a hemispherical damage zone of reduced p‐wave velocities beneath the crater (Raith et al. Forthcoming).…”
Section: Geophysical Surveying Of Experimental Impact Cratersmentioning
confidence: 99%
“…D P and D S have been particularly useful metrics to track changes in the degree of disruption extending radially from impacts into large target blocks. This is accomplished by measuring V P directly on samples cut from the shocked blocks (Ahrens & Rubin, 1993; Ai & Ahrens, 2007) or indirectly via wave speed tomography (Moser et al., 2013; Raith et al., 2018; Xia & Ahrens, 2001). D P has been particularly useful in connecting damage to attenuation and induced micro‐crack densities (Liu & Ahrens, 1997) in materials from these experiments, although these the magnitudes of these damage measures were not linked more directly to levels of strain experienced by the sample.…”
Section: Discussionmentioning
confidence: 99%